Country experiences in economic development, management and entrepreneurship : proceedings of the 17th Eurasia business and economics society conference - Bilgin, Mehmet Huseyin; Danis, Hakan; Demir, Ender; Can, Ugur (Springer Verlag, 2017)
This volume brings together selected papers from the 17th EBES Conference, organized in Venice in winter 2015. The theoretical and empirical papers present the latest research in diverse areas of business, economics, and finance from many different regions. They chiefly focus on the interactions between economic development, entrepreneurship and financial institutions, especially putting the spotlight on cross-country evidence. Topics range from women's entrepreneurship and economic regulation, to sustainability and climate change. This book provides researchers, professionals, and students a great opportunity to catch up on the latest studies in different fields and empirical findings on many countries and regions.
Keywords: Economic development -- Congresses.; Development economics -- Congresses.; elektronické knihy; electronic books